Proceedings of the 17th ACM Conference on Information and Knowledge Management 2008
DOI: 10.1145/1458082.1458140
|View full text |Cite
|
Sign up to set email alerts
|

Relating dependent indexes using dempster-shafer theory

Abstract: Traditional information retrieval (IR) approaches assume that the indexing terms are independent, which is not true in reality. Although some previous studies have tried to consider term relationships, strong simplifications had to be made at the very basic indexing step, namely, dependent terms are assigned independent counts or probabilities.In this study, we propose to consider dependencies between terms using Dempster-Shafer theory of evidence. An occurrence of a string in a document is considered to repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The Dempster-Shafer theory mentioned earlier remains one of the most widely used logical formalisms in IR. It has been applied to build a complete and holistic IR framework [25], but also to integrate Web evidence into IR [55], to integrate evidence of query difficulty into Web IR in the form of semantic scope [43], as well as to relate dependent indices of IR systems [47]. Finally, to our knowledge, the only prior use of Subjective Logic to IR has been the recent work of [34], who used it to model query difficulty as a subjective belief, formulated on the basis of various types of linguistic evidence.…”
Section: Formal Logic In Irmentioning
confidence: 99%
“…The Dempster-Shafer theory mentioned earlier remains one of the most widely used logical formalisms in IR. It has been applied to build a complete and holistic IR framework [25], but also to integrate Web evidence into IR [55], to integrate evidence of query difficulty into Web IR in the form of semantic scope [43], as well as to relate dependent indices of IR systems [47]. Finally, to our knowledge, the only prior use of Subjective Logic to IR has been the recent work of [34], who used it to model query difficulty as a subjective belief, formulated on the basis of various types of linguistic evidence.…”
Section: Formal Logic In Irmentioning
confidence: 99%
“…Particular aspects of formal logic have also been used to address specific aspects or processes in IR, for instance belief revision has been used to model IR agents [14], to estimate the similarity between a document and a query [15], and more recently to model adaptive and context-sensitive IR [13]. The Dempster-Shafer theory presented in Section 1 has been used extensively: to build an IR framework where information structure, significance, uncertainty and partiality can be elegantly represented and processed [12], to integrate Web evidence into IR [23], to integrate into Web IR evidence of query difficulty in the form of semantic scope (one of the types of evidence we used in this work) [18], as well as to relate dependent indices [20]. There are further applications of formal logic to IR, reviews of which can be found in [3].…”
Section: Related Workmentioning
confidence: 99%
“…From a multi-source information collaboration point of view, a variety of research concerning the usage of the Dempster-Shafer theory of evidence in ranking has been conducted [2][3][4].The Dempster-Shafer theory of evidence is utilized to retrieve documents using noun phrases [2]. Single terms and term sets are taken as indexing terms, and belief functions are used to rank documents [3]. Content and structure information is combined using Dempster's rule of combination [4].…”
Section: Introductionmentioning
confidence: 99%